Modelagem do desempenho em tração de conjuntos mecanizados visando ao dimensionamento do trator - Santos, Paula Machado dos (2010)
In pursuit of knowledge about the performance of agricultural tractors on the market and make the appropriate selection of attachments for each tractor, the research has presented mathematical models as an important tool in the representation of the traction performance of tractors. But that, however, Brazilian researchers found as the main limitation in applying these mathematical models using data characteristic of soil and machinery North American and European. By the need to obtain representative values of soil conditions and Brazilian machinery, the goal was to determine demand models for prediction of traction performance of tractors in operations that require traction force. Sets were used mechanized tractorseeding, disc harrow and chisel plow operating on two soil textures, loamy and silty. Seeking for a graphical representation of demand required traction force, slipage and fuel consumption was held to simulate the different mathematical models by the help of computer program Table Curve 3D v.2.03 (Jandel Scientific) and Table Curve 2Dv.2.03 (Jandel Scientific) capable of providing information for the empirical prediction of these parameters. It was found that the forward speed of the tractor directly influences the demand pull of all sets mechanized, differing from the model proposed by ASAE D497.2 (1995). The speed when interacting with the mass of the disk harrow represents the traction performance parameters using linear models, as well as its interaction with the working depth of the chisel plow by quadratic models with good fit, over 70%. The seeding showed an increase in demand of traction with the linear increase of tractor speed. Predictive theories Cn, Bn and Mn have good correlation with experimental values in soils typical Brazilian, corresponding on average 70% for values measured experimentally. Theory being the most Mn related behavior of energy demand and slipage action. New parameters are needed to estimate the traction force of tillers and planters, as well as the change of coefficients to characterize these machinery. As models for seeding, disc harrow and chisel plow: D = Fi. [1474 + (601.S)]. W.T , D = Fi. [290 + (57.S)]. W.T and D = Fi. [110 + (32.S) + (-2.9. S2)]. W.T, respectively.